2018
DOI: 10.1002/jper.18-0117
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant soft tissue status and crestal bone levels around adjacent implants placed in cigarette smokers and never smokers: Five‐year follow‐up results

Abstract: Background It is hypothesized that peri‐implant soft tissue inflammation and crestal bone loss (CBL) are higher around adjacent implants placed in cigarette smokers compared with never smokers. The aim of the present 5‐years follow‐up retrospective clinical study was to compare the peri‐implant soft tissue status and CBL around adjacent implants placed in cigarette smokers and never smokers. Methods Cigarette smokers (group 1) and never smokers (group 2) with adjacent dental implants were included. Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Some research compared both showed there was no statistical difference about the soft tissue around implant and alveolar bone absorption between smokers and non-smokers, and the implant success and survival rate can amount to 100%. 9,10 But the overwhelming consensus was that smokers have a higher rate of implant failure than nonsmokers. Vervaeke reported that implant bone loss in smokers was 1.18mm higher than that in non-smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research compared both showed there was no statistical difference about the soft tissue around implant and alveolar bone absorption between smokers and non-smokers, and the implant success and survival rate can amount to 100%. 9,10 But the overwhelming consensus was that smokers have a higher rate of implant failure than nonsmokers. Vervaeke reported that implant bone loss in smokers was 1.18mm higher than that in non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Of these patients, 166 (38.6%) had BMI index under 26, 227 (52.8%) range 26-30 and 37 (8.6%) above 30. The mean duration of symptoms was 5.8 years (range, [3][4][5][6][7][8][9][10][11][12]. 109 (25.3%) patients had history of smoking.…”
Section: Patient Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…CBL was measured only at baseline using bitewing radiographs (Ekta speed plus; Kodak) to confirm the diagnosis of peri‐implantitis. Baseline CBL was recorded as a linear distance from 2 mm below IAC to crest 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…Baseline CBL was recorded as a linear distance from 2 mm below IAC to crest. 29,30 These parameters were recorded at baseline and after 120 days.…”
Section: Clinical and Radiographic Investigationsmentioning
confidence: 99%
“…The MBL and CBL were defined as a lined distance from 2 mm below the cementoenamel junction and IAC, respectively, to the bony crest. 19,20…”
Section: Clinicoradiographic Assessmentmentioning
confidence: 99%